Preparing for the labour market and lifelong learning in Germany - Weiß, Reinhold [Verfasser] (My University, 2013)
The paper deals with the situation of youth employment and unemployment in Germany. The first chapter shows that in Germany youth unemployment is low in international terms. Then the two major challenges vocational education and training (VET) in Germany had to overcome during the past twenty years are described: the restructuring of VET in the East and West of the country after the reunification on the one hand and the demographic development on the other hand. The second chapter explains the reasons for the low level of youth unemployment. The third chapter gives an overview of the "various instruments that have been discussed and dismissed, piloted and introduced, modified over the years and sometimes abolished again" over the course of time aiming at reducing youth unemployment and helping young people to get qualified VET. Finally, three additional programs and special measures to combat youth unemployment are presented: (1) Improving the apprenticeship entry maturity of school leavers, (2) permanent adaptation of occupations to the requirements of the labour market, and (3) securing the attractiveness of dual VET. (Textauszug, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; G 1.2.2.4 Arbeitslosigkeit; L 5 Beratung & Orientierung; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; Berufsbildungspolitik; Duales System; Jugendarbeitslosigkeit; Beschäftigungsfähigkeit; Berufsorientierung; Durchlässigkeit im Bildungssystem